INFLUENCE OF MAKE A MATCH LEARNING MODEL ON STUDENT’S LEARNING RESULT IN GEOMETRIES IN SDN PEJATEN TIMUR 05 - Shinta Marda Putri; Dian Anggraeni Maharbid (Institut Pendidikan Indonesia, 2023)
Low mathematics learning outcomes are caused by various factors, one of which is the lack of use of varied learning models. One of the learning models that has the potential to improve learning outcomes is Make a Match Model. The purpose of this study is to determine the effect of the Make a Match learning model on the learning outcomes of Geometry Mathematics in elementary schools. This study used a quantitative approach, with the subject of 4th grade students of SDN Pejaten Timur 05. The research sample consisted of two classes, namely the experimental class and the control class totaling 60 students. In experimental class, there were 30 students, and the control class numbered 30 students. In obtaining data, researchers use the method of testing mathematics learning outcomes in the form of multiple-choices questions. The data analysis technique used is inferential analysis with hypothesis testing using t-test statistics, a significant level of 0.05. Based on the results of the study, it was found that the use of the Make a Match learning model affects the mathematics learning outcomes of multifaceted Geometry Materials. This is shown in the average score of the experimental class after being given the Make a Match learning treatment which is 84.00 and the control class given conventional learning treatment which is 70.17. The results of the hypothesis test obtained Sig. (2-thailed) values of 0.000 < 0.05, so it can be concluded that in this study H0 was rejected and Ha was accepted.